The predominant clonal evolution (PCE) concept of microbial pathogens and its practical usefulness - Tibayrenc, Michel (Henry Stewart Talks, 2007)
Recombination vs. clonality, Neo-Pasteurian era, Looking for the common denominator among parasitic protozoa, fungi, bacteria and viruses, PCE = salami slicing model, No PCE – frequent recombination: soup model, Recombinational load, The PCE concept, Linkage disequilibrium: restrained recombination, Near-clading, Parity between phylogenetic trees, Multilocus Sequence Typing (MLST), The “Russian doll” model, Practical implications of the PCE approach, The clonet concept, Revisiting the phylogenetic species concept (PSC), Applying the PCE approach to a given species
Updated at 2018/04/30